2020
DOI: 10.1002/essoar.10504116.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attenuation of ocean surface waves in pancake and frazil sea ice along the coast of the Chukchi Sea

Abstract: Buoy observations are used to calculate spectral attenuation rates of surface waves in pancake and frazil sea ice near the coast of Alaska • Consistently higher attenuation is observed near the ice edge than further in the ice cover • Attenuation rates follow a powerlaw dependence on frequency and are applicable to parametrization schemes in wave forecast models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Stopa et al (2018a) found difficulties in fitting single exponential curves to their SAR-derived wave heights and opted for piecewise fitting instead, with two very different exponential curves close to the ice edge and deeper inside of the MIZ. Strong dependence of attenuation on distance from the ice edge was also found by Hosěkováet al (2020). Recently, Huang and Li (2023) fitted exponential curves to satellite-derived profiles of wave heights (consisting of more than 10 data points), but high scatter in their data makes it difficult to estimate whether other functional forms would provide a better fit.…”
Section: Observations and Interpretation Of Wave Attenuation In Sea Icementioning
confidence: 83%
“…Stopa et al (2018a) found difficulties in fitting single exponential curves to their SAR-derived wave heights and opted for piecewise fitting instead, with two very different exponential curves close to the ice edge and deeper inside of the MIZ. Strong dependence of attenuation on distance from the ice edge was also found by Hosěkováet al (2020). Recently, Huang and Li (2023) fitted exponential curves to satellite-derived profiles of wave heights (consisting of more than 10 data points), but high scatter in their data makes it difficult to estimate whether other functional forms would provide a better fit.…”
Section: Observations and Interpretation Of Wave Attenuation In Sea Icementioning
confidence: 83%